The effectiveness of light emitting diodes on shoot regeneration in vitro from shoot tip tissues of Limnophila aromatica (Lamk.) Merr. and Rotala rotundifolia (Buch-Ham. ex Roxb) Koehne. (2nd April 2020) - Dogan, Muhammet
ABSTRACT: Light emitting diodes (LEDs) have become a promising technology for agriculture and horticulture. I investigated the effects of white (W), red (R) and blue (B) LED lights on the propagation of Limnophila aromatica (Lamk.) Merr. and Rotala rotundifolia (Buch-Ham. ex Roxb) Koehne using tissue culture. The shoot tip explants of L. aromatica and R. rotundifolia under different light environments were cultured in Murashige and Skoog (MS) basic nutrient medium with 6-benzylaminopurine (BAP) (0.05, 0.10 and 0.20 mg/l) and gibberellic acid (GA3 ) 0.25 mg/l) + kinetin (KIN) 0.25, 0.50 and 0.75 mg/l. The explants grown under combinations of white, red and blue LEDs were more effective for propagation of the plants in vitro. In L. aromatica, the maximum number of shoots/explant and the longest shoot lengths were obtained using the combination of white, red and blue LED lights in a 1:2:1 ratio in MS medium supplemented with 0.10 and 0.20 mg/l BAP. In R. rotundifolia, the maximum shoots/explant and shoot lengths were obtained in the explants using the combination of white, red and blue LED lights in a 1:2:1 ratio in the MS culture media fortified with 0.25 mg/l GA3 + 0.25 and 0.75 mg/l KIN. After the regenerated shoots were rooted, they were adapted successfully to external conditions. LEDs have significant advantages over fluorescent lights.